Efikasi Insektisida Gokilath-S50EC (d,d-transsifenotrin 50 g/l) terhadap Nyamuk Aedes aegypti dengan Metode Pengabutan (Thermal Fogging) - Firda Yanuar; Willem Sugiharto (ASPIRATOR - Journal of Vector-borne Disease Studies, 2018)
Dengue vector control is still relying on fogging using insecticides with solar solvents. This causes pollution due to the odors generated and residues left in the environment. It is necessary to look for alternative insecticides that no longer use solar as a solvent but use water such as Gokilath-S50EC. In this experiment, we tested the effectiveness of Gokilath-S50EC (d,d-trans-syphenotrin 50 g/l) with the aim to see the insecticidal efficacy of Aedes aegypti known as DHF vector. The sample test mosquito used is Ae. aegypti which comes from Pangandaran Lokalitbangkes as many as 25 females. Test mosquitoes were exposed to insecticides for 3-5 seconds with a method of fogging. The experimental results showed that mosquitoes tested fainting in the first 30 seconds after exposure to insecticides. The same results were shown when the solvent was added polyethylene-glycol (PEG). This time trial also measured droplet diameters at 1.0 mm and 1.2 mm nozzle with or without PEG. The test results showed that PEG increased the percentage of droplets of ≥ 50 µm in air and made the insecticide reach even further. Gokilath-S50EC insecticides are effective in killing Ae. aegypti by using water solvents, the addition of PEG will increase the reach of insecticides but not affect the effectiveness of insecticides.